Modified Limberg Flap Cover for Recurrent Sacrococcygeal Pilonidal Sinus: Our Experience at a Medical College In Nepal - Adhikari, Budhi Nath; Bhattarai, Abhishek; Devkota, Pragya; Khatiwada, Sushma (Birat Journal of Health Sciences, 2021)
Introduction: Pilonidal sinus is an inflammatory disease seen mostly in the intergluteal region of young males. Although any treatment strategy of this condition is generally free of life-threatening complications due to its superficial nature, it is still a feared disease because of recurrence which greatly increases the morbidity.Objective: To investigate the results of wide rhomboid excision and modified Limberg transposition flap reconstruction to treat recurrent pilonidal sinus.Methodology: Well-documented records of all patients with recurrent sacrococcygeal pilonidal sinus who underwent wide excision and a modified Limberg transposition flap at our center during the past 3 years and followed up for longer than 12 months were analyzed. The modification primarily consisted of an asymmetrically rotated rhomboid excision and lateralization of the lower midline. Patient demographics, days of hospitalization, complications, patient satisfaction and recurrence rates were evaluated.Result: Most patients in the study were overweight. No relationship was detected between BMI and number of sinus openings, hospital stay, drain placement or recurrences but an association with infection was noted. The number of pilonidal sinus orifices did not have a correlation with age, number of previous surgeries, duration of hospital stay or drains placement. The mean duration of hospitalization was 7.89 ± 3.41 days and the mean duration of suction drainage was 6.33±2.87 days. Half of our patients developed complications in the postoperative period. The only patient who developed superficial wound infection stayed the most in the hospital. All patients had some complaints regarding the operation site; however, they were satisfied with the result of the operation and had no recurrence at 12 months of follow-up.Conclusion: Rhomboid excision of recurrent sacrococcygeal pilonidal sinus with modified Limberg flap closure is a promising surgical technique with advantages of a good patient satisfaction and no recurrence after a year of surgery.